Identifying the effect of thickness on crack width in one-way reinforced concrete slab structures - Kridaningrat, Bhondana Bayu Brahmana; Soehardjono, Agoes; Wisnumurti; Nuralinah, Devi (Eastern-European Journal of Enterprise Technologies, 2024)
This paper presents an evaluation study of crack limit states according to design codes and previous research. It aims primarily to relate research findings to design code similarities. Cracks in reinforced concrete structures are still a challenging problem for researchers, especially in one-way plate structures where there is still a lot of damage and corrosion in the reinforcement due to cracks. Finding the right formula will make it easier for practitioners to design these structures, and the problem of durability in reinforced concrete plates can be overcome. From this research, an approach is proposed on how to predict the maximum crack width formula in one-way reinforced concrete slabs with different thicknesses. Plates use a variety of thicknesses, including 125 mm, 150 mm, 175 mm, and 200 mm. The test specimens have the same dimensions and steel reinforcement, a slab width of 0.6 m and a length of 2 m. From a literature study of prediction formulas from previous research works and codes, namely wmax(prop)=7.5*10-3 fsh-0.333, it was found that thickness (h) has little influence on maximum crack width. The results from both approaches in this analysis are overall in accordance with the observed experimental tests and the proposed formula. Based on these observations, increasing the thickness of the reinforced concrete slab has significantly reduced the maximum crack width so that the experimental formula is obtained, namely wmax(exp)=0.32*fsh-1.113. Therefore, a constant is needed to evaluate the influence of thickness parameters for slabs with a thickness less than 200 mm on the maximum crack width formula for reinforced concrete slabs, and a special approximation formula has been obtained. In practical use, the crack width formula can only be used for one-way slabs